A method for preparing a NiCoMnCuAl0.2 high-entropy alloy from positive and negative electrodes of a decommissioned NMC333 battery

CN118305316BActive Publication Date: 2026-10-16XI AN JIAOTONG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410411261.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-08
Publication Date
2026-10-16
Estimated Expiration
2044-04-08

AI Technical Summary

Technical Problem

这种回收方式周期长、能耗高、污染大且回收产品附加值低,使得退役三元锂离子电池回收工作可行性大幅下降

Benefits of technology

[0019]This invention first separates the positive and negative electrode materials and current collectors from retired NMC333 batteries using a calcination method. The powder obtained from calcination reduction is then passed through saturated CO2 water, stirred, and filtered to separate metallic Li and other metal elements. Next, the graphite negative electrode is removed by calcination in an air atmosphere. Equimolar amounts of aluminum and copper powders from the positive and negative electrode sheets are then mixed with nickel, cobalt, and manganese powders, and high-energy ball milled under an inert atmosphere to prepare a NiCoMnCuAl0.2 high-entropy alloy. This invention utilizes retired positive and negative electrode materials and sheets to prepare a high-value high-entropy alloy material. The process is relatively simple, has a short cycle time, high experimental repeatability, and a large yield with high added value. The molar ratios of nickel, cobalt, and manganese in the NMC333 battery used in this invention are similar, conforming to the material ratio requirements for high-entropy alloys. The prepared NiCoMnCuAl0.2 high-entropy alloy has great application and research prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118305316B_ABST
    Figure CN118305316B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing NiCoMnCuAl0.2 high-entropy alloy from positive and negative electrodes of retired NMC333 batteries, wherein the positive and negative electrode sheets disassembled from the retired NMC333 batteries are calcined at high temperature in an inert gas to separate the positive and negative electrode sheets and electrode powder, the obtained powder is dispersed in an excess saturated CO2 aqueous solution and fully stirred, and copper and aluminum current collectors are respectively ball milled into aluminum and copper powder with a diameter of less than 10 microns; aluminum and copper powder with a molar amount equal to that of nickel, cobalt and manganese in material B is added, and the stainless steel ball milling tank filled with inert atmosphere is loaded and ball milled to obtain the NiCoMnCuAl0.2 high-entropy alloy; the retired positive and negative electrode materials and electrode sheets are used to prepare high-entropy alloy materials with higher value, the process is relatively simple, the period is short, the experimental process has high repeatability, the output is large, and the added value is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of retired battery resource recycling, and relates to a method for preparing NiCoMnCuAl0.2 high-entropy alloys from the positive and negative electrodes of retired NMC333 batteries. Background Technology

[0002] With the rapid increase in global demand for new energy sources and the gradual phasing out of polluting traditional fossil fuels, the development of clean energy has become a crucial topic in scientific research. Lithium-ion batteries, with their advantages of cleanliness, high efficiency, light weight, high energy density, and long cycle life, are increasingly being used in the power sources of new hybrid and pure electric vehicles. Simultaneously, the widespread application of lithium-ion batteries has led to an unavoidable social problem: the large-scale generation of retired lithium-ion batteries. Among retired NMC333 lithium-ion batteries, the positive and negative electrodes hold the greatest recycling value. The lithium element contained in the positive electrode is currently a strategic metal resource, and its price has been rising year after year, thus possessing the greatest recycling value. However, the recycling of the remaining portion after the lithium extraction process mainly involves adjusting the pH to extract nickel, cobalt, and manganese in stages to obtain their corresponding metal salts. This recycling method is time-consuming, energy-intensive, polluting, and produces low-value-added recycled products, significantly reducing the feasibility of recycling retired ternary lithium-ion batteries. Developing simple, high-value-added recycled products has become a key scientific and engineering problem in the recycling of retired ternary lithium-ion batteries.

[0003] High-entropy alloys are composed of five or more metals in equimolar or near-equimolar amounts. Their diverse compositions and superior properties, such as extremely high thermal stability, unique magnetic properties, efficient lithium storage, and excellent catalytic performance, have attracted considerable interest from researchers. The disordered atomic distribution of high-entropy alloys gives them exceptional stability, and their properties can be tuned by altering their chemical composition, thus expanding their application range. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing NiCoMnCuAl0.2 high-entropy alloy from the positive and negative electrodes of retired NMC333 batteries, thereby utilizing retired positive and negative electrode materials and electrode sheets to prepare high-entropy alloy materials with higher value.

[0005] This invention is achieved through the following technical solution:

[0006] A method for preparing NiCoMnCuAl0.2 high-entropy alloys for the positive and negative electrodes of retired NMC333 batteries includes the following steps:

[0007] Step (1): The positive and negative electrode sheets disassembled from the retired NMC333 battery are calcined at high temperature in an inert gas to separate the positive and negative electrode sheets and the electrode powder, and aluminum-copper current collector and electrode powder are obtained. The aluminum-copper current collector is cleaned and set aside.

[0008] Step (2): Calcine the obtained powder at 600℃ for 4-6 hours in an inert atmosphere, then disperse the obtained powder in an excess saturated CO2 aqueous solution and stir thoroughly, filter and dry to obtain material B;

[0009] Step (3): The copper-aluminum current collector obtained in step (1) is ball-milled into aluminum and copper powders with a diameter of less than 10 μm;

[0010] Step (4): Add aluminum powder and copper powder in the same molar amounts as nickel, cobalt and manganese in material B to material B to obtain material C;

[0011] Step (5): Load material C into a stainless steel ball mill jar filled with an inert atmosphere and seal it;

[0012] Step (6): Install the stainless steel ball mill jar onto the ball mill, set the ball mill speed to 4000-450 rpm, the single ball milling time to 1-1.5 hours, with an interval of 30 minutes, repeat more than 12 times, and obtain NiCoMnCuAl0.2 high entropy alloy after ball milling.

[0013] Furthermore, in step (1), the temperature is increased to 450°C at 10°C / min and calcined for 1-3 hours.

[0014] Further, step (5) specifically involves adding material C into a stainless steel ball mill jar, placing the stainless steel jar in an inert atmosphere glove box, and sealing and tightening the stainless steel jar inside the glove box.

[0015] Furthermore, in step (2), the calcination atmosphere is N2, the heating rate is 10℃ / min, the calcination temperature is controlled at 600℃, and the holding time is 4-6h.

[0016] Furthermore, the stirring time in the water saturated with CO2 in step (2) is 24 hours.

[0017] Furthermore, in step (6), the grinding material in the stainless steel grinding jar is zirconium oxide.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] This invention first separates the positive and negative electrode materials and current collectors from retired NMC333 batteries using a calcination method. The powder obtained from calcination reduction is then passed through saturated CO2 water, stirred, and filtered to separate metallic Li and other metal elements. Next, the graphite negative electrode is removed by calcination in an air atmosphere. Equimolar amounts of aluminum and copper powders from the positive and negative electrode sheets are then mixed with nickel, cobalt, and manganese powders, and high-energy ball milled under an inert atmosphere to prepare a NiCoMnCuAl0.2 high-entropy alloy. This invention utilizes retired positive and negative electrode materials and sheets to prepare a high-value high-entropy alloy material. The process is relatively simple, has a short cycle time, high experimental repeatability, and a large yield with high added value. The molar ratios of nickel, cobalt, and manganese in the NMC333 battery used in this invention are similar, conforming to the material ratio requirements for high-entropy alloys. The prepared NiCoMnCuAl0.2 high-entropy alloy has great application and research prospects.

[0020] The process first recovers and converts the positive and negative electrode sheets and electrode powder of retired NMC333 batteries through heating separation and carbothermal reduction. Then, equimolar amounts of nickel-cobalt-manganese electrode powder and aluminum-copper powder from the electrode sheets are mixed and smelted to obtain NiCoMnCuAl0.2 high-entropy alloy.

[0021] This invention prepares a NiCoMnCuAl0.2 high-entropy alloy from the positive and negative electrodes of retired NMC333 lithium-ion batteries containing high-value metal elements through separation, carbothermal reduction, and high-energy ball milling. This perfectly combines the fields of retired battery resource recycling and high-entropy alloys, creating a new recycling method for retired battery resources. The experimental process is simple, has a short cycle time, requires no additives, expands the application of retired battery materials in the field of high-entropy alloys, and creates a new way to recycle battery materials for novel high-entropy alloy battery negative electrode materials. Attached Figure Description

[0022] Figure 1 X-ray diffraction pattern of the high-entropy alloy NiCoMnCuAl0.2;

[0023] Figure 2 Scanning electron microscope image of the high-entropy alloy NiCoMnCuAl0.2;

[0024] Figure 3 This is the elemental distribution diagram of the high-entropy alloy NiCoMnCuAl0.2. Detailed Implementation

[0025] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.

[0026] Example 1

[0027] A method for preparing NiCoMnCuAl0.2 high-entropy alloys for the positive and negative electrodes of retired NMC333 batteries includes the following steps:

[0028] The positive and negative electrode sheets disassembled from the retired NMC333 battery were calcined in N2 gas at a temperature of 10℃ / min to 450℃ for 1 hour to separate the positive and negative electrode sheets and electrode powder, and aluminum-copper current collector and electrode powder were obtained. The aluminum-copper current collector was cleaned and set aside for later use.

[0029] The obtained electrode powder was calcined at 600℃ for 4 hours in a N2 atmosphere at a rate of 10℃ / min to carry out a carbothermic reduction reaction. The obtained powder was then dispersed in an excess saturated CO2 aqueous solution and stirred for 24 hours. After filtration and washing several times to remove lithium, the powder was dried to obtain material B. The copper and aluminum current collectors were ball-milled into aluminum powder and copper powder with a diameter of less than 10μm, respectively.

[0030] Add aluminum powder and copper powder in equimolar amounts of nickel, cobalt, and manganese to material B to obtain material C. Add material C to a stainless steel zirconia ball mill jar. Place the stainless steel zirconia jar in an inert atmosphere glove box and seal the jar tightly inside the glove box. Remove the jar from the glove box and install it onto the ball mill for fixing and tightening. Set the ball mill speed to 4000-450 rpm, the single ball milling time to 1-1.5 hours, with a 30-minute interval, and repeat at least 12 times. After ball milling, a NiCoMnCuAl0.2 high-entropy alloy is obtained.

[0031] like Figure 1 As shown in the figure, it can be seen that... Figure 1 As shown, X-ray diffraction (XRD) analysis of the samples indicates that the diffraction peaks appearing at 2θ of approximately 43.7°, 50.5°, 74°, 89.6° and 95° correspond to the (111), (200), (220), (311) and (222) crystal planes, respectively, and the samples are all composed of a single fcc phase. Figure 2 The SEM sample preparation involved first gradually grinding the surface to the roughness of #2000 SiC sandpaper, followed by electrochemical polishing at room temperature using a 30V electrochemical polisher to obtain a final observable surface. The microstructure of the sample was then analyzed using scanning electron microscopy (SEM). Figure 3 SEM-EDS analysis revealed that Ni, Co, Mn, Cu, and Al elements were randomly and uniformly distributed in the fcc matrix phase.

[0032] Example 2

[0033] A method for preparing NiCoMnCuAl0.2 high-entropy alloys for the positive and negative electrodes of retired NMC333 batteries includes the following steps:

[0034] The positive and negative electrode sheets disassembled from the retired NMC333 battery were calcined in N2 gas at a temperature of 10℃ / min to 450℃ for 2 hours to separate the positive and negative electrode sheets and electrode powder, and aluminum-copper current collector and electrode powder were obtained. The aluminum-copper current collector was cleaned and set aside for later use.

[0035] The obtained electrode powder was calcined at 600℃ for 6 hours in a N2 atmosphere at a rate of 10℃ / min to carry out a carbothermic reduction reaction. The obtained powder was then dispersed in an excess saturated CO2 aqueous solution and stirred for 24 hours. After filtration and washing several times to remove lithium, the powder was dried to obtain material B. The copper and aluminum current collectors were ball-milled into aluminum powder and copper powder with a diameter of less than 10μm, respectively.

[0036] Add aluminum powder and copper powder in equimolar amounts of nickel, cobalt, and manganese to material B to obtain material C. Add material C to a stainless steel zirconia ball mill jar. Place the stainless steel zirconia jar in an inert atmosphere glove box and seal the jar tightly inside the glove box. Remove the jar from the glove box and install it onto the ball mill for fixing and tightening. Set the ball mill speed to 4000-450 rpm, the single ball milling time to 1-1.5 hours, with a 30-minute interval, and repeat at least 12 times. After ball milling, a NiCoMnCuAl0.2 high-entropy alloy is obtained.

[0037] Example 3

[0038] A method for preparing NiCoMnCuAl0.2 high-entropy alloys for the positive and negative electrodes of retired NMC333 batteries includes the following steps:

[0039] The positive and negative electrode sheets disassembled from the retired NMC333 battery were calcined in N2 gas at a temperature of 10℃ / min to 450℃ for 3 hours to separate the positive and negative electrode sheets and electrode powder, and aluminum-copper current collector and electrode powder were obtained. The aluminum-copper current collector was cleaned and set aside for later use.

[0040] The obtained electrode powder was calcined at 600℃ for 5 hours in a N2 atmosphere at a rate of 10℃ / min to carry out a carbothermic reduction reaction. The obtained powder was then dispersed in an excess saturated CO2 aqueous solution and stirred for 24 hours. After filtration and washing several times to remove lithium, the powder was dried to obtain material B. The copper and aluminum current collectors were ball-milled into aluminum powder and copper powder with a diameter of less than 10μm, respectively.

[0041] Add aluminum powder and copper powder in equimolar amounts of nickel, cobalt, and manganese to material B to obtain material C. Add material C to a stainless steel zirconia ball mill jar. Place the stainless steel zirconia jar in an inert atmosphere glove box and seal the jar tightly inside the glove box. Remove the jar from the glove box and install it onto the ball mill for fixing and tightening. Set the ball mill speed to 4000-450 rpm, the single ball milling time to 1-1.5 hours, with a 30-minute interval, and repeat at least 12 times. After ball milling, a NiCoMnCuAl0.2 high-entropy alloy is obtained.

Claims

1. A method for preparing NiCoMnCuAl0.2 high-entropy alloys for the positive and negative electrodes of retired NMC333 batteries, characterized in that... Includes the following steps: Step (1): The positive and negative electrode sheets disassembled from the retired NMC333 battery are calcined at high temperature in an inert gas to separate the positive and negative electrode sheets and the electrode powder, and aluminum-copper current collector and electrode powder are obtained. The aluminum-copper current collector is cleaned and set aside. Step (2): Calcine the obtained powder at 600℃ for 4-6 hours in an inert atmosphere, then disperse the obtained powder in an excess saturated CO2 aqueous solution and stir thoroughly, filter and dry to obtain material B; Step (3): The copper-aluminum current collector obtained in step (1) is ball-milled into aluminum and copper powders with a diameter of less than 10 μm; Step (4): Add aluminum powder and copper powder in the same molar amounts as nickel, cobalt and manganese in material B to material B to obtain material C; Step (5): Load material C into a stainless steel ball mill jar filled with an inert atmosphere and seal it; Step (6): Install the stainless steel ball mill jar onto the ball mill, set the ball mill speed to 4000-450 rpm, the single ball milling time to 1-1.5 hours, with an interval of 30 minutes, repeat more than 12 times, and obtain NiCoMnCuAl0.2 high entropy alloy after ball milling.

2. The method for preparing NiCoMnCuAl0.2 high-entropy alloy for the positive and negative electrodes of a decommissioned NMC333 battery according to claim 1, characterized in that: In step (1), the temperature is increased to 450℃ at 10℃ / min and calcined for 1-3 hours.

3. The method for preparing NiCoMnCuAl0.2 high-entropy alloy for the positive and negative electrodes of a decommissioned NMC333 battery according to claim 1, characterized in that: The specific step (5) involves adding material C into a stainless steel ball mill jar, placing the stainless steel jar in an inert atmosphere glove box, and sealing and tightening the stainless steel jar inside the glove box.

4. The method for preparing NiCoMnCuAl0.2 high-entropy alloy for the positive and negative electrodes of a decommissioned NMC333 battery according to claim 1, characterized in that: In step (2), the calcination atmosphere is N2, the heating rate is 10℃ / min, the calcination temperature is controlled at 600℃, and the holding time is 4-6h.

5. The method for preparing NiCoMnCuAl0.2 high-entropy alloy for the positive and negative electrodes of a decommissioned NMC333 battery according to claim 1, characterized in that: In step (2), the stirring time in the water saturated with CO2 is 24 hours.

6. The method for preparing NiCoMnCuAl0.2 high-entropy alloy for the positive and negative electrodes of a decommissioned NMC333 battery according to claim 1, characterized in that: In step (6), the grinding material in the stainless steel grinding jar is zirconium oxide.

Citation Information

Patent Citations

  • Method and system for efficiently recovering lithium from lithium ion battery positive electrode material

    CN111613847A

  • Recycling method of waste lithium ion battery positive electrode material

    CN111825110A